Visualizing MICP with X-ray μ-CT to enhance cement defect sealing. (July 2019) - Kirkland, Catherine M.; Norton, Drew; Firth, Olivia; Eldring, Joachim; Cunningham, Alfred B.; Gerlach, Robin; Phillips, Adrienne J.
Graphical abstract: An illustration of MICP formation in a wellbore cement defect. The resulting mineral seal could mitigate fluid leakage to functional aquifers or the atmosphere. Highlights: X-ray μ-CT shows spatio-temporal changes due to biomineralization of cement defects. Apparent permeabilities decreased following CaCO3 precipitation. Cement defect apertures decreased more than 97% in each biomineralized reactor. Faster injection and frequent nutrient pulses produced more CaCO3 in the defect. Control of reaction and transport rates may yield more homogeneous biomineralization. Abstract: Concerns about leakage exist when storing fluids like CO2 or natural gas in the subsurface given their potential to damage functional groundwater aquifers or be emitted to the atmosphere. Defects in the cement surrounding the wellbore undermine the integrity of subsurface storage systems. Microbially induced calcite precipitation (MICP) is a technique that uses low viscosity fluids and microorganisms (˜2 μm diameter) to seal defects like micro-annuli, cracks, and channels in well cement. This study quantified MICP in a cement channel defect using X-ray computed microtomography (X-ray μ-CT). Following control and replicate experiments conducted with a low injection flow rate, and which produced X-ray μ-CT data showing precipitation predominately occurred near the inlet, the injection strategy was modified for a third MICP experiment. The revised injection method used an increased flow rate and more frequent nutrient pulses resulting in 1) fewer calcium media pulses to seal the defect and 2) a more homogeneous distribution of mineral compared to the replicate experiments. Observations made during these experiments will aid in improving the safety and efficacy of subsurface fluid storage systems.